Perturbation of DNA replication and cell cycle progression by commonly used [3H]thymidine labeling protocols. - Hoy, C A (1990)
The effect of tritiated thymidine incorporation on DNA replication was studied in Chinese hamster ovary cells. Rapidly eluting (small) DNA from cells labeled with 2 microCi of [3H]thymidine per ml (200 microCi/mmol) for 60 min matured to a large nonelutable size within approximately 2 to 4 h, as measured by the alkaline elution technique. However, DNA from cells exposed to 10 microCi of [3H]thymidine per ml (66 microCi/mmol) was more rapidly eluting initially and did not mature to a nonelutable size during subsequent incubation. Semiconservative DNA replication measured by cesium chloride gradient analysis of bromodeoxyuridine-substituted DNA was also found to be affected by the final specific activity of the [3H]thymidine used in the labeling protocol. Dramatic cell cycle perturbations accompanied these effects on DNA replication, suggesting that labeling protocols commonly used to study DNA metabolism produce aberrant DNA replication and subsequent cell cycle perturbations.